Race, media, and the crisis of civil society : from Watts to Rodney King - Jacobs, Ronald N. (Cambridge University Press, 2000)
Comparing African-American and mainstream US newspaper coverage of some of the most important racial crises of the post-war period, this text argues that a strong African-American press is still needed today.
Keywords: African Americans and mass media.; Mass media and race relations -- United States.; African Americans in mass media.; African American press.; Mass media -- Social aspects -- United States.; United States -- Race relations.; Noirs américains et médias.; Médias et relations raciales -- États-Unis.; Noirs américains dans les médias.; Presse noire américaine.; Médias -- Aspect social -- États-Unis.; États-Unis -- Relations raciales.; SOCIAL SCIENCE -- Media Studies.; African American press; African Americans and mass media; African Americans in mass media; Mass media and race relations; Mass media -- Social aspects; Race relations; United States; Rassenunruhen; Massenmedien; Ethnische Beziehungen; USA; Schwärze; Massamedia.; Berichtgeving.; Oproeren.; Geschichte 1965-1992.; Samfundsvidenskab -- Sociologi.; Electronic books.